A clinical follow‐up of omalizumab in routine treatment of allergic asthma monitored by CD‐sens. Issue 3 (7th May 2018) - Johansson, S. Gunnar O.; Lilja, Gunnar; Hallberg, Jenny; Nopp, Anna
Abstract: Introduction: Omalizumab has been available for treatment of allergic asthma for more than a decade and thus, its efficacy in routine treatment was of interest to evaluate. Basophil allergen threshold sensitivity (CD‐sens) has been shown to correlate with the bronchial allergen threshold sensitivity and can be used to objectively measure omalizumab treatment efficacy. We aimed to evaluate the effect of omalizumab treatment of allergic asthma by CD‐sens, as an objective marker of the IgE‐mediated inflammation, and related to SPT, spirometry, FeNO, Asthma Control Questionnaire (ACQ), and Global Evaluation of Treatment Effectiveness (GETE). Methods: Thirty‐two patients were treated with omalizumab for 16 weeks. CD‐sens was used to define the response and related to clinical parameters. If CD‐sens was negative (<0.1) (CD‐sens low Group) the patient continued with the standard dose. If CD‐sens was ≥0.1 (CD‐sens high Group) a second 16 weeks period with 25–50% dosage increase was started and evaluated after a total of 32 weeks. Results: Nine of 32 patients became CD‐sens negative after treatment (CD‐sens start: 8.0; 16 weeks: <0.01) and regarded as successful. 15/23 were unsuccessful (CD‐sens start: 13; 16 weeks: 1.65) and the omalizumab dose was increased. CD‐sens decreased significantly ( p  < 0.05) and further 3/15 patients became CD‐sens negative (CD‐sens at 32 weeks: 0.5). There was a significantly smaller IgE‐ab fraction (IgE‐ab/IgE) in the CD‐sens low versus the CD‐sens high Group ( p  < 0.0001). A significant decrease in ACQ was seen in both groups after 16 weeks treatment ( p  = 0.05 and 0.01, respectively). No significant changes could be detected for the other clinical parameters. Conclusion: By the use of the objective laboratory method CD‐sens, which effectively measure the direct effect of omalizumab, that is, the IgE‐mediated part of the allergic asthma, in combination with clinical parameters it might be possible to more effectively monitor and treat IgE‐mediated allergic asthma. Abstract : This study highlights the difficulties in evaluating omalizumab treatment effect and the importance of combining different diagnostic methods, both immunological and clinical. By the use of the objective laboratory method CD‐sens which effectively measure the direct effect of omalizumab that is, the IgE‐mediated part of the allergic asthma, in combination with clinical parameters, it might be possible to more effectively monitor and treat IgE‐mediated allergic asthma.